Strain and microstructures of GaN epilayers with thick InGaN interlayer grown by MOCVD. (15th March 2017) - Liu, Jianxun; Liang, Hongwei; Liu, Yang; Xia, Xiaochuan; Huang, Huolin; Tao, Pengcheng; Sandhu, Qasim Abbas; Shen, Rensheng; Luo, Yingmin; Du, Guotong
Abstract: GaN epilayers with thick InGaN interlayer are grown by metal-organic chemical vapor deposition on sapphire substrates. The as-grown GaN films with an InGaN interlayer show remarkable relaxed compressive strain measured by Raman spectroscopy. The microstructures within the InGaN interlayer were investigated by high resolution transmission electron microscopy. It indicated that the misfit dislocations and stacking faults in the InGaN interlayer formed, which is responsible for the relaxation of the lattice strain. In addition, the InGaN interlayer was found to terminate most of threading dislocation from the GaN pseudosubstrate layer even though the strain relaxation occurs. Such data help to provide further insight into the strain relaxation mechanisms and improve the quality of GaN films and the performance of GaN related devices.